Green Marketing and Its Impact on Customer Loyalty: The Chain Mediation of Emotional Desire and Satisfaction - Pramadanti, Rindika; Masrina Gultom; Rusman Effendi Sihombing (Jurnal Dinamika Manajemen, 2025)
This study aims to examine the influence of green marketing, brand image, and emotional desire on customer satisfaction and loyalty at McDonald’s. The novelty of this research lies in integrating the psychological factor of emotional desire with green marketing and brand image within a single framework, which has rarely been tested simultaneously in the fast-food industry. A quantitative approach with a survey method was employed, involving 225 purposively selected respondents who had made at least two purchases. The data were analyzed using SmartPLS. The findings reveal that green marketing, brand image, and emotional desire significantly affect customer satisfaction. Furthermore, brand image and emotional desire have a direct positive impact on customer loyalty, while emotional desire also exerts an indirect effect on loyalty through satisfaction. In contrast, green marketing and brand image show no indirect influence through satisfaction on loyalty. From a managerial perspective, the results suggest that McDonald’s should combine green marketing strategies with brand image reinforcement and emotional engagement, as these factors play a crucial role in improving customer satisfaction and building long-term loyalty.